Survei Sarana dan Prasarana Olahraga di Sekolah Dasar Negeri Se-Kelurahan Jungkat Kabupaten Mempawah - Qosim, Anang; Hardika, Nevi; Zamuri, Muhammad; Salahuddin (Universitas PGRI Pontianak, 2022)
The purpose of this paper is to find out the ideal standard of sports facilities and infrastructure in State Elementary Schools in Jungkat District, Mempawah Regency. The method used in this research is a descriptive selection method in the form of a survey. The techniques used to collect data in this study were direct observation techniques, direct communication techniques and documentary studies, while the tools used to collect data in this study were observation sheets, interview sheets and documentation. The population in this study used a saturated sample. The data analysis technique in this study used a frequency distribution. The results of the study concluded that sports facilities and infrastructure in State Elementary Schools in Jungkat Village, Mempawah Regency did not meet the criteria for the ideal standard of sports facilities and infrastructure based on the Minister of National Education Regulation No. 24 of 2007. 2021 provides an average of 30.06% and an ideal standard. The ownership of facilities and infrastructure in State Elementary Schools in the Jungkat District is the property of the school. The feasibility of the facilities and infrastructure of State Elementary Schools in the District of Jungkat, Mempawah Regency is included in the Less category.